2010
DOI: 10.1002/cne.22532
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific gene expression in early postnatal mouse thalamus

Abstract: Previous studies in the developing mouse thalamus have demonstrated that regional identity is established during early stages of development (Suzuki-Hirano et al. J. Comp. Neurol. 2011;519:528-543). However, the developing thalamus often shows little resemblance to the anatomical organization of the postnatal thalamus, making it difficult to identify genes that might mediate the organization of thalamic nuclei. We therefore analyzed the expression pattern of genes that we have identified as showing regional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 49 publications
12
68
2
1
Order By: Relevance
“…In amphibians and amniotes, the prethalamus is further characterized by expression of the proneural bHLH genes, Olig2 and Mash1, and a GABAergic neurotransmitter phenotype (Andrews et al, 2003;Brox et al, 2003;Os orio et al, 2010;Yuge et al, 2011). Our unpublished data and results of previous studies confirmed that zebrafish olig2 and ascl1a are expressed in the embryonic prethalamus Mueller, 2002, 2004b;Tiso et al, 2009;Scholpp et al, 2009) and GABAergic neurons were also found (Mueller et al, 2006).…”
Section: Molecular Characterization Of the Prethalamussupporting
confidence: 90%
See 1 more Smart Citation
“…In amphibians and amniotes, the prethalamus is further characterized by expression of the proneural bHLH genes, Olig2 and Mash1, and a GABAergic neurotransmitter phenotype (Andrews et al, 2003;Brox et al, 2003;Os orio et al, 2010;Yuge et al, 2011). Our unpublished data and results of previous studies confirmed that zebrafish olig2 and ascl1a are expressed in the embryonic prethalamus Mueller, 2002, 2004b;Tiso et al, 2009;Scholpp et al, 2009) and GABAergic neurons were also found (Mueller et al, 2006).…”
Section: Molecular Characterization Of the Prethalamussupporting
confidence: 90%
“…Both in zebrafish and mouse, the two thalamic progenitor domains translate during development into different functional domains with neurons of different neurotransmitter phenotypes. pTH-R contributes to GABAergic and pTH-C to glutamatergic neurons that are specified by ascl1a/ Mash1 and ngn1/Ngn2 pathways, respectively (Mueller et al, 2006;Vue et al, 2007Vue et al, , 2009Scholpp et al, 2009;Os orio et al, 2010;Yuge et al, 2011). These comparative data suggest a conservation of rostral and caudal thalamic progenitor domains in zebrafish and mouse.…”
Section: Rostral and Caudal Thalamic Domainsmentioning
confidence: 75%
“…However, both Foxp2 and CTGF showed different expression patterns in neonatal marmoset brain. High-level expression of Foxp2 expression in mouse cortex in layer 6b and some additional staining was observed in somatosensory layer 4 (Yuge et al, 2011). In neonatal marmoset PFC, we observed strong expression of Foxp2 in layer 6, but in more caudal regions, the expression in layer 6 became weaker, and expression in layers 5 and 4 became much stronger (data not shown).…”
Section: Primate-specific Gene Expression In the Pfcmentioning
confidence: 64%
“…1), whose expression has been reported in mouse thalamus (Suzuki-Hirano et al, 2011;Yuge et al, 2011). Kitl, Ntng2, and Zic1 showed strong expression in the pulvinar and medial geniculate body (MG) (Fig.…”
Section: Gene Expression In Afferent Regions Of the Pfc-pulvinarmentioning
confidence: 78%
“…To investigate the expression pattern of genes that showed prominent thalamic expression in greater detail, we performed ISH for these transcripts at embryonic day (E)10.5, E12.5, and E15.5 and at postnatal day (P)6. In a companion paper, we describe a number of genes that show restricted expression in different regions of the thalamus (Yuge et al, 2011). In this paper, we report the expression patterns of genes that show particularly prominent and selective expression in the embryonic thalamic ventricular zone (VZ) and thalamic mantle zone, with a focus on genes that show prominent regionally restricted expression within the mantle zone.…”
Section: Introductionmentioning
confidence: 98%